Development and evaluation of diltiazem hydrochloride controlled-release pellets by fluid bed coating process - Mikkilineni Bhanu Prasad; Suryadevara Vidyadhara; Reddyvalam Lankapalli C Sasidhar; Talamanchi Balakrishna; Pavuluri Trilochani (Wolters Kluwer Medknow Publications, 2013)
The aim of the present study was to develop controlled-release pellets of diltiazem HCl with ethyl cellulose and hydroxylpropyl methylcellulose phthalate as the release rate retarding polymers by fluid bed coating technique. The prepared pellets were evaluated for drug content, particle size, subjected to Scanning Electron Microscopy (SEM) and Differential Scanning Calori metry (DSC), and evaluated for in vitro release. Stability studies were carried out on the optimized formulations for a period of 3 months. The drug content was in the range of 97%-101%. The mean particle size of the drug-loaded pellets was in the range 700-785 μm. The drug release rate decreased as the concentration of ethyl cellulose increased in the pellet formulations. Among the prepared formulations, FDL10 and FDL11 showed 80% drug release in 16 h, matching with USP dissolution test 6 for diltiazem HCl extended-release capsules. SEM photographs confirmed that the prepared formulations were spherical in nature with a smooth surface. The compatibility between drug and polymers in the drug-loaded pellets was confirmed by DSC studies. Stability studies indicated that the pellets were stable.